2015
DOI: 10.17116/sudmed201558230-31
|View full text |Cite
|
Sign up to set email alerts
|

The immunohistochemical study of the structures of the cardiac conduction system in the case of death from alcoholic cardiomyopathy

Abstract: The objective of the present study was to study the morphological criteria for toxic cardiopathy with the use of histological and immunohistochemical methods. The results of immunohistochemical studies of the sinoatrial node---???---(SAN) and the working myocardium in the patients presenting with alcoholic cardiomyopathy (ACMP) are presented. It was shown that vimentin expression in the SAN structures and the contractile myocardium is slightly increased whereas the expression of sarcomeric actin is decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Vimentin expression detected by immunohistochemistry is slightly increased in the SAN structures and the contractile myocardium in cases of cardiomyopathy induced by alcohol. [ 56 ] In addition, Gong et al [ 57 ] reported that the serum level of vimentin is correlated with the presence and severity of coronary artery disease in patients and they reported also that vimentin stimulates atherogenesis in ApoE −/− mice. An addition of this study that the intermediate microfilament proteins increase in tissue is due to the increase in their gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin expression detected by immunohistochemistry is slightly increased in the SAN structures and the contractile myocardium in cases of cardiomyopathy induced by alcohol. [ 56 ] In addition, Gong et al [ 57 ] reported that the serum level of vimentin is correlated with the presence and severity of coronary artery disease in patients and they reported also that vimentin stimulates atherogenesis in ApoE −/− mice. An addition of this study that the intermediate microfilament proteins increase in tissue is due to the increase in their gene expression.…”
Section: Discussionmentioning
confidence: 99%